An arachnid's guide to being an ant: morphological and behavioral mimicry in ant-mimicking spiders. (10th December 2022) - Subramaniam, Nimish; Tamma, Krishnapriya; Uma, Divya
Abstract: Batesian mimicry imposes several challenges to mimics and evokes adaptations in multiple sensory modalities. Myrmecomorphy, morphological and behavioral resemblance to ants, is seen in over 2000 arthropod species. Ant-like resemblance is observed in at least 13 spider families despite spiders having a distinct body plan compared to ants. Quantifying the extent to which spiders' shape, size, and behavior resemble model ants will allow us to comprehend the evolutionary pressures that have facilitated myrmecomorphy. Myrmaplata plataleoides are thought to closely resemble weaver ants, Oecophylla smaragdina. In this study, we quantify the speed of movement of model, mimic, and non-mimetic jumping spiders. We use traditional and geometric morphometrics to quantify traits such as foreleg size and hindleg size, body shape between the model ant, mimic, and non-mimics. Our results suggest that while the mimics closely resemble the model ants in speed of movement, they occupy an intermediate morphological space compared to the model ants and non-mimics. Ant-mimicking spiders are better at mimicking ants' locomotory movement than morphology and overall body shape. Some traits may compensate others, suggesting differential selection on these mimetic traits. Our study provides a framework to understand the multimodal nature of mimicry and helps discern the relative contributions of such traits that drive mimetic accuracy in ant-mimicking spiders. Abstract : Mimicry provides a textbook example of adaptation by natural selection. Ant-like resemblance is observed in 13 spider families despite spiders having a distinct body plan compared to ants. Jumping spiders, Myrmaplata plataleoides, closely resemble weaver ants, Oecophylla smaragdina. We quantified movement, leg size and body shape of model ants, mimics, and non-mimics. Our results suggest that ant-mimicking spiders are better at mimicking ants' movement, than their morphology and overall body shape.